2015
DOI: 10.4067/s0718-381x2015000100014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tumor Associated Tissue Eosinophilia (TATE) in Oral Squamous Cell Carcinoma Using Carbol Chromotrope Stain

Abstract: Tumor related tissue eosinophilia (TATE) is a known phenomenon but its role in prognostics and correlation with size of the primary tumor is still controversial. Using a stain, like Carbol chromotrope, that targets eosinophils exclusively and vividly, offers an advantage over haematoxylin and eosin, which was used in most of the studies. Forty-nine cases of oral squamous cell carcinoma, where the TNM staging has been recorded in their history, was taken and stained with Lendrum's carbol chromotrope. Significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There was elevated TATE in stages III and IV, so increased eosinophilia was associated with T3 and T4, suggestive of increased eosinophil count with increased primary tumor size. Celestina Dawn Peter et al 32 have also reported an increase in eosinophil count with an increase in the tumor size. Oliveira et al 9 showed absent/mild eosinophils in early clinical stages, i.e., stages I and stage II while significantly higher eosinophilia was seen in stages III and IV, suggesting increased eosinophilia with increasing clinical stages.…”
Section: Discussionmentioning
confidence: 92%
“…There was elevated TATE in stages III and IV, so increased eosinophilia was associated with T3 and T4, suggestive of increased eosinophil count with increased primary tumor size. Celestina Dawn Peter et al 32 have also reported an increase in eosinophil count with an increase in the tumor size. Oliveira et al 9 showed absent/mild eosinophils in early clinical stages, i.e., stages I and stage II while significantly higher eosinophilia was seen in stages III and IV, suggesting increased eosinophilia with increasing clinical stages.…”
Section: Discussionmentioning
confidence: 92%
“…[12] In HNSCC, the presence of eosinophils in the stromal infiltrate ranges between 22% and 89%. [13] This stromal eosinophilic infiltrate in tumors is termed as tumor-associated tissue eosinophilia (TATE). TATE was first described by Prezewoski in 1896 in carcinoma of the uterine cervix as “eosinophilic stromal infiltration of a tumor not associated with tumor necrosis or ulceration.”[14] TATE is characterized by the presence of eosinophils as a component of peritumoral and intratumoral inflammatory infiltrate.…”
Section: Introductionmentioning
confidence: 99%
“…[5] These multifunctional, multifaceted leukocytes play a key role in health and disease, are also involved in the pathogenesis, inflammatory processes, infectious diseases, tissue injury, tumor immunity, and allergic reactions. [6] Infiltration of eosinophils in the tumor environment plays an important role in biological behavior of cancer such as carcinoma stromal interactions. Tumor-associated tissue eosinophilia (TATE) is characterized by the presence of eosinophils as a component of peritumoral and intratumoral inflammatory infiltrate.…”
mentioning
confidence: 99%
“…Hence, in this study, carbol chromotrope was used, with a benefit that it selectively and vividly stains eosinophils. [6] The aim of this study is to compare the tissue eosinophils in OSCC and normal tissue and to correlate the expression of TATE in different grades of OSCC.…”
mentioning
confidence: 99%